Microscopic Polyangiitis with Pulmonary Fibrosis: An Often-Recognized Manifestation of the Disease - Liam M. Clifford; Jamma Li; Christopher J. Renaud; Suran L. Fernando (Case Reports in Rheumatology)
Background. Microscopic polyangiitis (MPA) can manifest with atypical features such as pulmonary fibrosis and chronic obstructive pulmonary disease (COPD), which are atypical and unusual features of small vessel vasculitis. Case Presentation. This paper presents two patients with microscopic polyangiitis and respiratory symptoms attributable to atypical pulmonary manifestations. Pulmonary fibrosis was present in both cases, with COPD also present in one patient. Management involved methylprednisone, prednisone, and cyclophosphamide. The second patient also received azathioprine. Both patients responded well to immunosuppressive treatment; however, pulmonary fibrosis and COPD were refractory to immunosuppression. Conclusion. Pulmonary manifestations including pulmonary fibrosis, emphysema, and bronchiectasis are observed in MPA. Evaluation of MPA in unexplained cases should be performed to avoid delays in diagnosis and management. Patients who present with MPA with pulmonary manifestations may respond to treatment, but their pulmonary features demonstrate a refractory nature to such management.